2010
DOI: 10.1371/journal.pone.0012935
|View full text |Cite
|
Sign up to set email alerts
|

Protective Action of Resveratrol in Human Skin: Possible Involvement of Specific Receptor Binding Sites

Abstract: BackgroundResveratrol is a plant-derived polyphenol with purported protecting action on various disorders associated with aging. It has been suggested that resveratrol could exert its protective action by acting on specific plasma membrane polyphenol binding sites (Han Y.S., et al. (2006) J Pharmacol Exp Ther 318:238–245). The purpose of this study was to investigate, in human skin, the possible existence of specific binding sites that mediate the protective action of resveratrol.Methods and FindingsUsing huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
4
42
0
2
Order By: Relevance
“…The keratinocyte colonies are subject to auto-regulation and can be recreated in 2D cell cultures [24,25]. The immortalized HaCat cells still maintain the main characteristics of keratinocytes [26][27][28][29]. The capability of HaCat cells to colonise and proliferate was heavily depended on initial seeding densities.…”
Section: Discussionmentioning
confidence: 99%
“…The keratinocyte colonies are subject to auto-regulation and can be recreated in 2D cell cultures [24,25]. The immortalized HaCat cells still maintain the main characteristics of keratinocytes [26][27][28][29]. The capability of HaCat cells to colonise and proliferate was heavily depended on initial seeding densities.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in order to elicit its cutaneous activity, resveratrol should permeate into the inner skin layers and in particular in the epidermis, where the majority of resveratrol binding sites that mediated its activity are located [3,4,9,11]. In order to enhance the cutaneous availability of resveratrol, delivery systems such as liposomes and nanoparticles have been designed [1,4,10,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (3,5,4'-trihydroxystilbene), a naturally occurring polyphenolic compound produced by a variety of plants [1,2], is a potent antioxidant which has been shown to exhibit anti-inflammatory, anti-carcinogenic and anti-microbial properties, together with cardioprotective and neuroprotective activities [1,3,4]. In addition to these array of beneficial pharmacological effects, the topical application of resveratrol has been reported to exert a therapeutic action against several cutaneous pathologies such as oxidative damage (e.g., oxidative DNA damage, lipid peroxidation) mediated by excessive formation of free radicals and other reactive species (non-radical oxygen species), inflammation, microbial infections, skin cancer and damage induced by the solar UV radiation [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…84 As far as skin is concerned, resveratrol has been recently shown to possess a protective action in vitro against cell death after exposure of HaCaT cells to the nitric oxide free radical donor sodium nitroprusside. 85 Furthermore, Giardina et al reported in 2010 that in experiments in vitro with skin fibroblasts treated with resveratrol there was a dose-related increase in the rate of cell proliferation and in inhibition of collagenase activity. 86 Steinberg showed that resveratrol oligomers hopeaphenol, epsilon-viniferin, R2-viniferin, ampelopsin inhibit the growth number of human tumor cell lines significantly stronger than resveratrol itself.…”
Section: Resveratrol (Stilbenes)mentioning
confidence: 99%